Analisis Kesiapan Psikologis Pasangan dalam Menghadapi Pernikahan - Aini, Hidayati; Afdal, Afdal (Jurnal Aplikasi IPTEK Indonesia, 2020)
Divorce is a long-standing problem and still often has an impact on family members. Divorce often begins with various conflicts resulting from a lack of psychological readiness in the face of marriage. Therefore, researchers conducted research related to the analysis of the psychological readiness of couples in the face of marriage. The research method uses a quantitative approach to descriptive methods. The subject of this study was a couple who were getting married and were conducting screening at the religious affairs office of Padang City. The study subjects were taken using a purposive sampling technique of 150 people consisting of 75 men and 75 women. The research instrument was developed from the Theory of Fowers & Olson (1989) using a poll of likert scale models. The study findings showed the picture of psychological readiness in the face of marriage in men was at a high category of 45.33% and women were in the high category by 48%. The results of this study are input for counselors one of them through prenuptial counseling in an effort to improve the psychological readiness of couples in the face of marriage.